Religion and Sex Crimes in Baroque Spain: The Ave Maria as Alibi in His Wife’s Executioner by María de Zayas - Nelson, Bradley (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2018)
The focus of this essay is Zayas’s use of the Ave Maria, a hymn or prayer that celebrates the immaculate purity of God’s chosen vessel for the birth of Christ and then pleads with her to “pray for us sinners now and in the hour of our death”. I will claim that Zayas’s arguably blasphemous use of the religious hymn, which is situated within her ironic use of the Christian theology of revelation, pulls the curtain back on a morally bankrupt aristocratic class that has bent theological thought and religious ritual toward the perpetuation and defense of sexual violence in early modern Spanish social and political institutions.